Adam B. Chambers, The Revised Ordinances of the City of Saint Louis, Revised and Digested by the Fifth City Council during the First Session, Begun and Held in the City of St. Louis, on the Second Monday of May, A. D. 1843. with the Constitutions of the United States and the State of Missouri, and the City Charter Page 304, Image 305 (1843) [Ordinances of Kansas City,] Misdemeanors, § 10. - (:unkn) unknown (General Publisher, 1843)
Every person who shall discharge any cannon or other ordinance, or fire off any carbine, fusil, rifle, musket, gun, pistol, or other arms, or set off any squib or cracker, or fly any kite in the air, within the city, shall be deemed guilty of a misdemeanor. This section shall not apply to the firing of salutes by any military corps, or to the firing of salutes upon any occasion of general public interest.
--
Keywords: DISCHARGE